Formulation for Enhancement of Rate of In Vitro Drug Release Profiles of Poorly Soluble Rilpivirine Hydrochloride by Spray Drying Technique (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of the present research work was to enhance the rate of in vitro drug release profiles of poorly solubleRilpivirine Hydrocloride (RH) by Spray drying technique. Rilpivirine is a non-nucleoside reverse transcriptaseinhibitor of human immunodeficiency virus type-1 (HIV-1). Method: RH is belongs to BCS class-II. It is insolublein water and practically insoluble across the pH range of 1 â€“ 7.5. One of the major concerns with the formulationof RH is its poor solubility, which results into poor bioavailability after oral administration. Spray drying techniquehas been proven to be an efficient technique for conversion of poorly soluble crystalline form into highly solubleamorphous form and make it useful for formulating lab scale batches to commercial batches. Hence, Spray dryingtechnique was chosen for reducing the % of crystallinity / or converting crystalline form into highly solubleamorphous form by spray drying technique. The organic dispersion comprising RH, hydrophilic carriers likeSoluplus / Kollidon VA64 / Kolliphor SLS / Kolliphor P407 / Kollidon 30 at different ratios along with finer gradeof microcrystalline cellulose (Avicel PH 105) was subjected to spray drying using Buchi spray dryer. Results &Discussion: The dissolution profiles of formulated product (RT2 & RT3) in FDA recommended dissolution mediawas compared against the dissolution profiles of corresponding innovator product. The rate of in vitro drug releasewas at faster and complete from test product as compared to Innovator product profiles i.e., EUDRANTâ„¢ 25 mgtablets. From the characterization of spray dried powder RSD8 by DSC and XRD concluded that % crystallinity ofRH was reduced significantly. Conclusion: The obtained results suggested that Spray drying technique might bean efficacious approach in enhancing the therapeutic potential of Rilpivirine Hydrochloride.